Palestine - Sacco, Joe (Fantagraphics, 2024)
"In the early 1990s, in the waning days of the First Intifada, or uprising, against the Israeli occupation, Joe Sacco spent two months with Palestinians in East Jerusalem, the West Bank, and the Gaza Strip. He listened to their stories and recorded what he saw, and the result was Palestine, a landmark work of comics journalism and first-person chronicle that has taken readers worldwide into the turbulent streets, the loving homes, and the squalid refugee camps of the Palestinian people."--